Gut microbiota-derived metabolites mediate the neuroprotective effect of melatonin in cognitive impairment induced by sleep deprivation - Xintong Wang; Zixu Wang; Jing Cao; Yulan Dong; Yaoxing Chen (Microbiome, 2023)
Abstract Background Sleep loss is a serious global health concern. Consequences include memory deficits and gastrointestinal dysfunction. Our previous research showed that melatonin can effectively improve cognitive impairment and intestinal microbiota disturbances caused by sleep deprivation (SD). The present study further explored the mechanism by which exogenous melatonin prevents SD-induced cognitive impairments. Here, we established fecal microbiota transplantation, Aeromonas colonization and LPS or butyrate supplementation tests to evaluate the role of the intestinal microbiota and its metabolites in melatonin in alleviating SD-induced memory impairment.  Results Transplantation of the SD-gut microbiota into normal mice induced microglia overactivation and neuronal apoptosis in the hippocampus, cognitive decline, and colonic microbiota disorder, manifesting as increased levels of Aeromonas and LPS and decreased levels of Lachnospiraceae_NK4A136 and butyrate. All these events were reversed with the transplantation of SD + melatonin-gut microbiota. Colonization with Aeromonas and the addition of LPS produced an inflammatory response in the hippocampus and spatial memory impairment in mice. These changes were reversed by supplementation with melatonin, accompanied by decreased levels of Aeromonas and LPS. Butyrate administration to sleep-deprived mice restored inflammatory responses and memory impairment. In vitro, LPS supplementation caused an inflammatory response in BV2 cells, which was improved by butyrate supplementation. This ameliorative effect of butyrate was blocked by pretreatment with MCT1 inhibitor and HDAC3 agonist but was mimicked by TLR4 and p-P65 antagonists.  Conclusions Gut microbes and their metabolites mediate the ameliorative effects of melatonin on SD-induced cognitive impairment. A feasible mechanism is that melatonin downregulates the levels of Aeromonas and constituent LPS and upregulates the levels of Lachnospiraceae_NK4A136 and butyrate in the colon. These changes lessen the inflammatory response and neuronal apoptosis in the hippocampus through crosstalk between the TLR4/NF-κB and MCT1/ HDAC3 signaling pathways. Video Abstract